High-throughput DNA microarray characterisation and molecular analysis of resistance to mupirocin, fusidic acid and linezolid in Methicillin-Resistant Staphylococcus aureus : populations in Irish hospitals 1971-2010 - Brennan, Orla (Trinity College (Dublin, Ireland). School of Dental Science, 2013)
Methicillin-resistant Staphylococcus aureus (MRSA) is a major pathogen of humans and animals and can express multiple virulence and antimicrobial resistance genes. In Ireland, detailed molecular typing showed that different clonal types of nosocomial MRSA prevailed at different time periods over the last 40 years, with highly clonal ST22-MRSA-IV currently predominant. Informative typing plays a vital role in preventing the spread of MRSA. However, typing methods including pulsed-field gel electrophoresis (PFGE), mulitlocus-sequence typing (MLST), staphylococcal cassette chromosome mec (SCCmec) typing, spa and dm typing examine only small sections of the genome and often are not sufficiently discriminatory for epidemiological investigations, especially with isolates that exhibit limited genetic diversity. Furthermore, these approaches are not readily ameanble to high-througput screening or to outbreak investigations in real-time and do not detect virulence or resistance genes. The aims of the present study were three-fold. Firstly to investigate the usefulness of the high- throughput StaphyType DNA microarray (Alere, Germany) for genotyping diverse MRSA strains and for differentiating between ST22-MRSA-IV isolates. This array can detect 334 S. aureus genes and alleles, including species-specific, antimicrobial resistance, and virulence-associated genes, as well as markers used for typing. Secondly, due to the increasing prevalence of high-level mupirocin resistance (Hi-MupR) and fusidic acid resistance among Irish MRSA the associated genotypes and mechanisms of resistance were investigated. Thirdly, detailed molecular characterisation was undertaken of the first ST8-MRSA- IVa/USA300 MRSA isolate found by array screening to harbour the multidrug resistance gene cfr.
Keywords: Dental Science, Ph.D.; Ph.D. Trinity College Dublin